Factors Affecting Elementary School Teacher Performance: A SEM-PLS Review - Teni Susanti; Yunus Abidin (Jurnal Ilmiah Sekolah Dasar, 2023)
One important factor in improving the quality of education is teacher performance. However, teacher performance remains a problematic topic. This is particularly true when it comes to factors that technically affect their performance. Therefore, this study aimed to analyze factors that contribute most to teacher performance. This study was conducted using a correlational survey method. Data source in this study was 120 elementary school teachers participated voluntarily. The data were collected through an online questionnaire based on a Likert scale. They were processed using SEM-PLS. The results showed that the most influential factor in shaping teacher performance was competence. School climate, principal leadership and social influence have no significant relationship with teacher performance. Based on the results, improving competence is one effective to improve teacher performance. In addition, the other factors such as principal leadership, school climate, motivation, social influence, and teacher’s opportunity also affect teacher performance, albeit not significant. Through supportive school climate, high motivation and social support, teachers are hoped to show steady improvement to their performance. With better teacher performance it is hoped that educational progress will be achieved.